Actual versus Optimal Fisheries Policies: An Evaluation of the Cod Fishing Policies of Denmark, Iceland and Norway - Ragnar Arnason; Leif K. Sandal; Stein Ivar Steinshamn; Niels Vestergaard (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2005)
Many ocean fisheries are subject to a fundamental economic problem generally referred to as the common property problem. The common property problem manifests itself as excessive fishing fleets and fishing effort, depressed fish stocks and little or no profitability of the fishing activity, irrespective of the richness of the underlying marine resources. European fisheries represent some of the most dramatic examples of the common property problem. This paper employs simple empirical models and recently developed mathe-matical techniques to find optimal feed-back policies to examine the economic efficiency of three European fisheries, namely the Danish, Icelandic and Nor-wegian cod fisheries. The optimal harvesting policies for each of these fisheries are calculated. Comparing these optimal policies with actual harvests provides a measure of the relative efficiency in these three cod fisheries. The comparison confirms that the cod harvesting policies of these three coun-tries have been hugely inefficient in the past. Moreover, it appears that the inef-ficiency has been increasing over time. Only, during the last few years of our data are there indications that this downward trend may have been halted. This comparative improvement, slight as it is, may reflect the impact of a more re-strictive fisheries policy since the early 1990s.
Keywords: 330; Fischereipolitik; Seefische; Vergleich; Wirkungsanalyse; Dänemark; Island; Norwegen